Nina Estimasi Angkutan Sedimen Dasar pada Saluran Sand Trap Daerah Irigasi Gumbasa: Estimation of Bedload Sediment Transport at Sand-trap Channel of Gumbasa Irrigation Area - Rustiati, Nina; Fauzi, Nurfahli Riza; Keristiadi, Ariesto; Setiaji, Wahyu; Ngaripin (Jurnal Teknik Sumber Daya Air, 2023)
The Sulawesi River Basin Office 3 requires data on the characteristics of sediment grains to predict the frequency of sedimentation flushing. The Gumbasa Irrigation Area is located in the Palu valley area which extends from the headwaters of the Gumbasa River to the Kawatuna River in Palu City, namely: Gumbasa, Tanambulaya, Dolo, Sigi Biromaru and South Palu Districts. The Gumbasa Irrigation Area has an area of ​​1,737 Ha. This study aims to determine the amount of bedload sediment transport in the Sand Trap Channel of the Gumbasa Irrigation Area. In this research, bed load sampling, flow velocity and water depth in the channel were taken. Sampling was carried out in two seasons, namely at the beginning of the rainy season (February) and the end of the rainy season (March). The purpose of taking samples at two different times is to determine the difference in the amount of sediment transport at that time. The sediment samples are then tested in the laboratory to obtain grain diameter measurements with a passing percentage of 90% and 50% (D90 and D50). The data that has been obtained is then analyzed using the Meyer-Peter-Muller equation. The analysis results show that the amount of bedload sediment transport at the beginning of the rainy season using the Meyer-Peter-Muller equation is 184,966 m3/day, while at the end of the rainy season the amount of bedload sediment transport using the Meyer-Peter-Muller equation is 38,494 m3/day.